2017
DOI: 10.1371/journal.pone.0187811
|View full text |Cite|
|
Sign up to set email alerts
|

Lung and heart-lung transplantation in pulmonary arterial hypertension

Abstract: BackgroundReal use of lung (LT) and heart-lung (HLT) transplantation in pulmonary arterial hypertension (PAH) is unknown. The objectives were to describe the indication of these procedures on PAH treatment in a national cohort of PAH patients, and to analyze the potential improvement of its indication in severe patients.MethodsEligibility for LT/HLT was assessed for each deceased patient. Incident patients from REHAP diagnosed between January 2007 and March 2015 and considered eligible for LT/HLT were grouped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Oxygen therapy would be added if SpO2 <90% [ 31 ]. Judicious use of diuretics is crucial to reduce volume overload without consequent hypotension (due to reduced cardiac output as the right heart is preload dependent), arrhythmias (due to hypokalemia), and metabolic alkalosis [ 23 , 25 , 27 , 29 ]. As such, renal function and blood biochemistry were regularly monitored when bumetanide and metolazone were added to our patient’s regimen, and she was treated with supplemental potassium as necessary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Oxygen therapy would be added if SpO2 <90% [ 31 ]. Judicious use of diuretics is crucial to reduce volume overload without consequent hypotension (due to reduced cardiac output as the right heart is preload dependent), arrhythmias (due to hypokalemia), and metabolic alkalosis [ 23 , 25 , 27 , 29 ]. As such, renal function and blood biochemistry were regularly monitored when bumetanide and metolazone were added to our patient’s regimen, and she was treated with supplemental potassium as necessary.…”
Section: Discussionmentioning
confidence: 99%
“…As such, renal function and blood biochemistry were regularly monitored when bumetanide and metolazone were added to our patient’s regimen, and she was treated with supplemental potassium as necessary. Studies have shown that acutely administered inotropic drugs, such as digoxin, have improved cardiac output in IPAH; however, its long-term effects remain unknown [ 25 , 27 , 30 ]. The role of anticoagulation in IPAH is controversial as the evidence in favor was derived from small, retrospective, and single-center studies [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is growing evidence to support the use of PAH therapies in PAH associated with CHD (PAH-CHD) population, but despite recent advances, mortality remains high. Patients with severe PAH with an inadequate response to PAH therapy should be considered for transplantation [4]. We present the case of a patient with severe PAH and a large secundum atrial septal defect (ASD), who was referred to transplantation due to inadequate response to PAH therapy.…”
Section: Introductionmentioning
confidence: 99%